TRACES OF SEISMIC ACTIVITY IN THE LAKE BOTTOM SEDIMENTS OF EASTERN FENNOSCANDIA - S. B. Nikolaeva (Геодинамика и тектонофизика)
This paper presents the results of a study on traces of ancient earthquakes in the lake bottom sediments of eastern Fennoscandia (Kola region and Karelia). Based on the sediment cores from six lake basins located within large active structures of the region, consideration is being given to the most typical features of sedimentation affected by neotectonic movements of the Earth’s crust. The data presented here provide lithological-stratigraphical, paleobotanical and chronometrical evidence for lakes. The paper causes and mechanisms of formation of seismic structures in bottom sediments and their distinction from deformations of another origin.Generalized earthquake history in provided an opportunity to organize the existing information on the time of paleoearthquake manifestations and distinguish three active periods in paleoseismicity. These are Late Glaciation-Early Holocene marked by the most rapid uplift after the retreat of the last ice sheet (13500–8100 cal yr BP), Middle Holocene (6800–6600 cal yr BP), and Late Holocene (3100–200 cal yr BP). The results of this study showed that the number and intensity of seismic events changed at different stages of sedimentation. Since the Younger Dryas, fault zones (or their segments) have been repeatedly activated. Combined with the data on paleoseismicity in adjacent parts of Fennoscandia, our studies indicate an irregular pattern of the Late Pleistocene-Holocene seismic activity in stable areas formerly covered by glaciers. The obtained data make further adjustments to the neogeodynamic and seismic estimates of intraplate areas.